Gambaran status reproduksi pada sapi perah melalui pengukuran progesteron susu dengan metoda elisa - M.A. Setiadi; Adnin Adnan (Hemera Zoa, 1991)
Determination of reproduction status was carried out 16 lactation dairy coes at Faculty of Veterinary of Animal Science - IPB by measurement of milk progesteron level by Enzyme Immunoassay.This result could concluded that : oestrus, post oestrus and pregnant, respectively, where as 7 cows were oestrus, I Cow post oestrus, 3 cows dubius pregnant and 5 cows pregnant. Comfirmation by rectal palpation was done one week later and shown that : 4 of 5 diagnosed pregnant, I cows need recheck.The accuracy of milk progesteron assay by Enzyme Immunoassay (EIA) in this case was 80% for positive pregnant.